Heat stress memory in Porites lutea: Holobiont coordination and the molecular basis of thermotolerance - Yuling Ma; Xiaopeng Yu; Kefu Yu; Yue Zheng; Biao Chen; Zhenjun Qin; Zhiheng Liao; Lijia Xu; Yongzhi Wang (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Associations of pedogenic carbonate accumulation with soil organic-inorganic carbon coupling in arid croplands - Tongping Lu; Yuling Li; Xuhui Wang; Hui Guo; Bin He; Muhammad Shoaib Rana; Jie Ma; Changyan Tian; Jianfei Shi; Yugang Wang; Xiujun Wang (Agriculture, Ecosystems & Environment, 2026)

Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Seawater eDNA and Underwater Visual Surveys Reveal Genus-Level Reef-Building Coral Communities in the Wanshan Archipelago, South China Sea - Jiabin Guo; Lan Yang; Zhihui Qin; Anxin Lu; Yuling Ma; Yue Zheng; Biao Chen; Zhenjun Qin; Zhiheng Liao; Lijia Xu; Yongzhi Wang; Kefu Yu; et al. (Fishes, 2026)
Environmental DNA (eDNA) metabarcoding is increasingly used as a complementary tool for coral biodiversity assessment, but its performance in subtropical, estuary-influenced reef systems remains insufficiently tested. This study combined seawater eDNA metabarcoding with concurrent underwater visual surveys and historical records to assess reef-building scleractinian corals in the Wanshan Archipelago, Pearl River Estuary. In June 2022, surface and bottom seawater samples were collected from seven sites, yielding 14 eDNA samples, and dive-based photographic surveys were conducted concurrently. A universal 18S rRNA assay was used for high-throughput sequencing, and eDNA detections were compared with visual and historical survey data at the genus level. eDNA detected 13 families and 21 genera, with Porites and Echinopora as dominant genera. eDNA recovered more genera than concurrent visual surveys in all five regional comparisons, although the two methods yielded overlapping but partly distinct genus inventories. Surface-water eDNA showed a slight, site-dependent advantage in genus recovery and overlap with concurrent visual surveys, whereas correspondence with historical records varied among regions; surface and bottom samples shared most genera but also contributed complementary layer-specific detections. Community composition showed spatial clustering broadly consistent with geographic proximity. These findings indicate that seawater eDNA provides complementary genus-level information and support paired surface- and bottom-water sampling for a more complete exploratory characterization of coral diversity in complex subtropical coastal reef systems.

Adaptive mechanisms of scleractinian corals against low-salinity stress: Insights from molecular regulation and natural acclimation in the Pearl River Estuary - Lijia Xu; Junling Chen; Yongzhi Wang; Yuling Ma; Yue Zhen; Biao Chen; Zhenjun Qin; Zhiheng Liao; Xiaopeng Yu; Kefu Yu (Journal of Environmental Sciences, 2026)

Effect of heat-moisture modified sweet potato starch on the microstructure and physicochemical properties of wheat noodles - Wei Wang; Dongdong Huang; Yuling Ma; Yiying Yang; Aijun Hu; Haiyan Gao (Journal of Cereal Science, 2026)

Antibacterial mechanisms of terpinen-4-ol against Aeromonas hydrophila - Kaiqi Lian; Xiangfeng Meng; Yuhang Wang; Shengming Ma; Xiaolong Li; Ren Ren; Yuling Liu; Lingling Zhou; Renhai Peng (Archives of Microbiology, 2026)

Long-term trends and risk regulation of heat exposure in megacities: seasonal dynamics and determinants - Ziwen Jin; Shuyi Zhang; Ke Zeng; Muyao Ma; Yue Yang; Yuling Fu; Hanxin Tang; Shan Yin; Ji Zheng; Min Liu (Environment, Development and Sustainability, 2026)

Vibration transmission characteristics of Camellia oleifera tree under excitation - Qingsong Li; Daochun Xu; Yuling Zhang; Xiaopeng Bai; Wenbin Li; Yuan He; Yuewei Ma (Computers and Electronics in Agriculture, 2026)

Molecular attribute-driven hybrid SEI engineering for durable silicon anodes - Yijie Lin; Yingkang Deng; Yuling Fu; Mingjun Ma; Haolei Chen; Xinqi Chen; Shuhan Chen; Jiarong He; Lidan Xing; Weishan Li (Chemical Engineering Journal, 2026)

Improving embryo rescue efficiency in seedless grape breeding with zeatin - Xi Chen; Shaopeng Zhao; Xinyu Chen; Mengyu Ma; Xue Wen; Yao Xiao; Yong Wang; Yuling Li; Feng Sun; Guotian Liu; Tingting Chen; Yan Xu (Protoplasma, 2026)

Characteristics of soil organic carbon and its stability under different vegetation types and restoration years in Hongze lake wetland, China - Yanan Bai; Haikun Wu; Huifeng Lu; Yuling Yang; Yanping Wang; Lei Dai; Yuchun Ma; Jinqi Wang; Yuzhi Song; Lidong Shen (Journal of Environmental Management, 2026)

Metagenomic and metabolomic insights into microbial-metabolite interactions underlying flavor formation in Hebei-style soybean paste fermentation - Chang Liu; Jingjing Hao; Han Lu; Pingping Ma; Yannan He; Yuling Xue; Zhiyuan Kang; Shijie Wang (Food Research International, 2026)

Corrigendum to “Zein nanoparticles in emerging food packaging: Mechanistic insights into self-assembly, structural driving forces, and functional applications” [Trends in Food Science & Technology 167 (2026) 105447] - Jawad Ashraf; Jiyao Zhang; Tabussam Tufail; Muhammad SafiUllah Virk; Ma Yuling; Muhammad Awais; Zahoor Ahmed; Zhou Sumei; Bin Xu (Trends in Food Science & Technology, 2026)

Zein nanoparticles in emerging food packaging: Mechanistic insights into self-assembly, structural driving forces, and functional applications - Jawad Ashraf; Jiyao Zhang; Tabussam Tufail; Muhammad SafiUllah Virk; Ma Yuling; Muhammad Awais; Zahoor Ahmed; Zhou Sumei; Bin Xu (Trends in Food Science & Technology, 2026)

Preparation of omniphobic membrane by anchoring hydrophobic islands at fixed-points for treating hypersaline wastewater - Ronghua Ma; Xiaolong Lu; Jie Gu; Kai Ren; Yuling Ren; Yuefei Song; Zhong Ma (Desalination, 2025)

Confinement-effect adsorbents based on titanium-based lithium ion sieve for efficient lithium adsorption under natural pH conditions - Yuling Ma; Yu Han; Yan Yang; Tao Zhang; Jinxin Yao; Yuchen Li; Yongchen Zong; Wei Wang (Chemical Engineering Journal, 2025)

The impact of COVID-19 pandemic on the etiological spectrum of respiratory infections in children - Jing Wang; Yuling Han; Xiaoling Wei; Yanqin Liu; Hua Zhang; Xiang Ma (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Genome-Wide Identification of the DVR Gene Family and Expression Analysis of GDF8 Genes in Qihe Gibel Carp - Jinyan Shan; Yuling Liu; Kaiqi Lian; Xianghui Xiao; Jun Ma; Ren Ren; Xiaolong Li; Guoqiang Wei; Youyi Kuang; Renhai Peng (Fishes, 2025)
(1) Background: The BMP/GDF (Bone Morphogenetic Protein/Growth Differentiation Factor) subfamily (Decapentaplegic-Vg1-related, DVR) within the transforming growth factor beta (TGF-β) superfamily plays critical roles in governing biological developmental processes and physiological functions. (2) Methods: In this study, we systematically investigated the DVR gene family in hexaploid Qihe gibel carp (Carassius gibelio var. Qihe) through comprehensive genomic identification, phylogenetic analysis, chromosome mapping, and cis-regulatory element prediction. The experimental design for gene expression analysis involved collecting samples from multiple tissues (brain, muscle, liver, kidney, etc.) and different developmental stages (20, 45, and 60 days post hatching, dph) to examine the expression patterns of four GDF8 genes using quantitative real-time PCR (qRT-PCR). (3) Results: We identified 50 DVR members in Qihe gibel carp. Phylogenetic analysis classified the 50 DVR family members into 20 distinct protein types, with 29 BMPs (Bone Morphogenetic Proteins) and 21 GDFs (Growth Differentiation Factors) identified. All 50 DVR proteins of Qihe gibel carp have similar TGF-β domains except for four BMP1 proteins. Chromosomal localization revealed widespread distribution of DVR members across 36 chromosomes, a pattern potentially linked to the hexaploid genome of Qihe gibel carp. Genes within the same subgroup exhibited conserved intron–exon architectures and similar intron numbers; syntenic conservation within subgroups may reflect functional constraints after polyploidization, implying evolutionary pressure to maintain functional domains. Through spatiotemporal expression profiling, we uncovered functional divergence among four GDF8 (myostatin) paralogs: GDF8-1 and GDF8-2 were predominantly expressed in brain and muscle tissues (dorsal and caudal), while GDF8-3 and GDF8-4 showed hepatic, cerebral, and renal specificity. Intriguingly, all paralogs exhibited a gradual upregulation during late development (20–60 days post hatching, dph), with peak expression staggered between 45 dph (GDF8-1/2) and 60 dph (GDF8-3/4). (4) Conclusions: These findings suggest that GDF8 plays a critical regulatory role in the growth and development of Qihe gibel carp. Collectively, these results provide a foundation for further investigations into the functional roles of the DVR gene family during the ontogenetic development of this species.

Novel insights into the morphological effects of trace organic contaminants on water/PhAC selectivity in nanofiltration of sewage - Junhao Zhao; Yanan Wang; Zuqiong Jiang; Yuefei Song; Nan Deng; Yuling Ren; Ronghua Ma; Kai Jiang (Journal of Hazardous Materials, 2025)

Fe/Mo synergistic confinement in controlled N-doped carbon nanotubes frameworks: Multiscale insights and octogen degradation in multisolvent systems–performance, interfacial mechanisms, and electronic optimization - Junlan Tang; Jinmao Ma; Panpan Zhou; Jihui Zhang; Xiaojun Wang; Yuqian Shi; Jiaming Xu; Xiangru Zhou; Yuling Bai; Jiade Lin; Chi Chen; Lincheng Zhou; et al. (Chemical Engineering Journal, 2025)

Influence of supports in CuFe-based catalysts for hydrogenation of CO2 to ethanol - Yangqin Liu; Yuling Ma; Xin Pu; Xin Han; Lei Ye; Lingtao Kong; Jiangbing Li; Jian Zhang; Haitao Xu; Xinglong Qin; Jichang Liu (Fuel, 2025)

Correction to: Failure mechanism and stability evaluation of rockslides with oblique intersecting faults as well as mitigation measures for slope − top platform collapse - Huaixin Li; Changgen Yan; Yuling Shi; Hengxing Lan; Han Bao; Weifeng Sun; Zhe He; Dingle Ma; Kui Wen; Jiamin Hu (Landslides, 2025)

How many trees are there in China? - Kai Cheng; Haitao Yang; Yuling Chen; Zekun Yang; Yu Ren; Yixuan Zhang; Danyang Lin; Weiyan Liu; Guoran Huang; Jiachen Xu; Mengxi Chen; Zhiyong Qi; et al. (Science Bulletin, 2025)

Isotopic and hydrochemical evidence for the origins of unconventional gases in the Middle and Lower Jurassic coal measures in the Fukang area of Junggar Basin, NW China - Jie Xiang; Jiandong Li; Xianqing Li; Xiaomin Ma; Jie Sun; Zhuo Zou; Yuling Qin (International Journal of Coal Geology, 2025)

A high-static-low-dynamic stiffness wire rope isolator with a magnetic negative stiffness device: Experiment, analytical method, and optimization - Shilong Yang; Wei Fan; Yuling Liu; Lingfei Ma; Zhengqing Chen (Engineering Structures, 2025)

Failure mechanism and stability evaluation of rockslides with oblique intersecting faults as well as mitigation measures for slope − top platform collapse - Huaixin Li; Changgen Yan; Yuling Shi; Hengxing Lan; Han Bao; Weifeng Sun; Zhe He; Dingle Ma; Kui Wen; Jiamin Hu (Landslides, 2025)

An AP2/ERF transcription factor GhERF109 negatively regulates plant growth and development in cotton - Huiyun Shi; Ghulam Qanmber; Zuoren Yang; Yuling Guo; Shuya Ma; Sheng Shu; Yujun Li; Zhongxu Lin; Fuguang Li; Zhao Liu (Plant Science, 2025)

Differential physiological and microbial responses of the octocoral Junceella squamata to high-temperature and cadmium stress - Xu Gao; Junling Chen; Yuling Ma; Yue Zheng; Yinyao Bu; Xiaopeng Yu; Kefu Yu (Marine Environmental Research, 2025)

Constructing a low-cost total Ce(III)-based adsorbent for efficient removal and recovery of phosphate - Tao Zhang; Junle Li; Dongqing Liu; Yuling Ma; Yu Han; Sujie Shan; Kai Sun; Elena V. Zelinskaya; Aijie Wang; Hongliang Sun; Wei Wang (Chemical Engineering Journal, 2025)

Effective enhancement of ramie anaerobic continuous flow degumming by chitosan and its microbiological mechanism - Xuehui Xie; Yiting Qin; Haonan Mo; Zhuoyu Zhao; Yuling Li; Yanxue Ma; Yao Sun; Dongyang Li; Ziyi Wu; Na Liu; Qingyun Zhang; Xiaoguang Chen (Bioresource Technology, 2025)

Nuclear factor NF-YA4a regulates salt stress tolerance and juvenile-adult phase transition in Pyrus - Yingjie Yang; Yuling Mei; Xueping Li; Ran Wang; Chunhui Ma; Jiankun Song; Zhenhua Cui; Jianlong Liu; Xiaozhi Zhou; Dingli Li (Horticulture, Environment, and Biotechnology, 2025)

Eliminating the effect of pH: Dual-matrix modulation adsorbent enables efficient lithium extraction from concentrated seawater - Yu Han; Liuqian An; Yan Yang; Yuling Ma; Hongliang Sun; Jinxin Yao; Tao Zhang; Wei Wang (Water Research, 2025)

Oil/water interface behavior of hesperidin methylchalcone and its application in nano-emulsions - Yuxiang Wang; Benguo Liu; Yuling Ma; Chunyan Wang; Hanjun Ma; Sheng Geng (Food Chemistry, 2025)

Selective ion channel adsorbents facilitate efficient and low environmental impact extraction of liquid lithium resources - Yu Han; Yan Yang; Yuling Ma; Daxin Liang; Liping Wen; Jun Ma; Wei Wang (Journal of Hazardous Materials, 2024)

Lactobacillus plantarum LP104 improved intestinal and brain inflammation by modulating TLR4 pathway and gut flora in alcohol liver injury mice - Yue Zhang; Yuxuan Ma; Yuling Fan; Yuexin Gao; Yamei He; Yu Wang; Bo Nan; Jingsheng Liu; Xia Li; Yuhua Wang (Food Bioscience, 2024)

Potential adaptation of scleractinian coral Pocillopora damicornis during hypo-salinity stress caused by extreme pre-flood rainfall over south China - Junling Chen; Xiaopeng Yu; Kefu Yu; Biao Chen; Zhenjun Qin; Zhiheng Liao; Yuling Ma; Lijia Xu; Yongzhi Wang (Environmental Research, 2024)

Comparative analysis of anaerobic degumming effects on different bast fibers from the angle of enzyme activity and microbial community structure - Yiting Qin; Xuehui Xie; Haonan Mo; Yuling Li; Xiaoguang Chen; Yanxue Ma; Zhuoyu Zhao; Hangmi Zheng; Yao Sun; Dongyang Li; Ziyi Wu; Na Liu; et al. (Journal of Cleaner Production, 2024)

Design, construction and evaluation of collaborative bio-system of Vibrio fluvialis with Chlorella sorokiniana for treating actual printing and dyeing wastewater - Yuling Song; Lijun Wang; Xi Qiang; Menglin Guo; Wenhui Gu; Songcui Wu; Shan Gao; Xuehua Liu; Xiujun Xie; Quancheng Fan; Jing Zhang; Zengling Ma; et al. (Chemical Engineering Journal, 2024)

Epidemiologic trends and changes in humoral immunity and lymphocyte subsets levels among hospitalized children with Mycoplasma pneumoniae infection during 2019–2023 - Linyan Tang; Kaiwen Zheng; Lanlan Ma; Ling Chen; Yuling Zhao; Li Li; Ke Wang; Jing Zhang; Xing Chen (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Design, construction and application of algae-bacteria synergistic system for treating wastewater - Weihao Li; Lijun Wang; Xi Qiang; Yuling Song; Wenhui Gu; Zengling Ma; Guangce Wang (Journal of Environmental Management, 2024)

Eliminating adverse effects of fouling layer using composite membranes with dense surface layers for sustainable membrane distillation of high-strength wastewater - Peizhi Wang; Jiawei Cheng; Jinxin Yao; Yuling Ma; Chuandong Wu; Dan Song; Wei Cheng; Jun Ma; Wei Wang (Desalination, 2024)

Early-relief effects of tetrahedral DNA nanostructures-assisted depression therapy via modulates hippocampal neurogenesis and neuroplasticity - Yikai Dou; Xiao Yang; Yue Du; Weitong Cui; Yuling Luo; Jinxue Wei; Liansheng Zhao; Xiaoxiao Cai; Xiaohong Ma; Yunfeng Lin (Chemical Engineering Journal, 2024)

Heterogeneous variations in wintertime PM2.5 sources, compositions and exposure risks at urban/suburban rural/remote rural areas in the post COVID-19/Clean-Heating period - Zhiyong Li; Zhuangzhuang Ren; Chen Liu; Zhi Ning; Jixiang Liu; Jinming Liu; Zhen Zhai; Xiaohua Ma; Lan Chen; Yuling Zhang; Longkai Bai; Shaofei Kong (Atmospheric Environment, 2024)

Weakened black carbon trans-boundary transport to the Tibetan Plateau during the COVID-19 pandemic - Ye Zhou; Junhua Yang; Shichang Kang; Yuling Hu; Xintong Chen; Mian Xu; Mengmeng Ma (Science of The Total Environment, 2024)

Mortality risk of people living with HIV under hypothetical intervention scenarios of PM2.5 and HIV severity: a prospective cohort study - Shujuan Yang; Chuanteng Feng; Teng Fei; Dan Wu; Liao Feng; Fengshun Yuan; Yao Fu; Hua Ma; Bin Yu; Li Liu; Yizhuo Li; Yiping Li; et al. (Science of The Total Environment, 2024)

Unveiling China’s natural and planted forest spatial–temporal dynamics from 1990 to 2020 - Kai Cheng; Haitao Yang; Hongcan Guan; Yu Ren; Yuling Chen; Mengxi Chen; Zekun Yang; Danyang Lin; Weiyan Liu; Jiachen Xu; Guangcai Xu; Keping Ma; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Equal importance of humic acids and nitrate in driving anaerobic oxidation of methane in paddy soils - Yanan Bai; Yanping Wang; Lidong Shen; Bo Shang; Yang Ji; Bingjie Ren; Wangting Yang; Yuling Yang; Zhiguo Ma; Zhaozhong Feng (Science of The Total Environment, 2024)

Diverse and high pollution of microplastics in seasonal snow across Northeastern China - Hanxuan Wen; Han Xu; Yuling Ma; Chunyu Zhang; Daizhou Zhang; Xin Wang (Science of The Total Environment, 2024)

Correction: The States of Different 5-HT Receptors Located in the Dorsal Raphe Nucleus Are Crucial for Regulating the Awakening During General Anesthesia - HaiXiang Ma; LeYuan Gu; YuLing Wang; Qing Xu; Yuanli Zhang; WeiHui Shao; Qian Yu; XiTing Lian; Lu Liu; JiaXuan Gu; Na Ji; XiaoLing Liu; et al. (Molecular Neurobiology, 2023)

The States of Different 5-HT Receptors Located in the Dorsal Raphe Nucleus Are Crucial for Regulating the Awakening During General Anesthesia - HaiXiang Ma; LeYuan Gu; YuLing Wang; Qing Xu; Yuanli Zhang; WeiHui Shao; Qian Yu; XiTing Lian; Lu Liu; JiaXuan Gu; Na Ji; XiaoLing Liu; et al. (Molecular Neurobiology, 2023)

Calculation of carbon emission efficiency in China and analysis of influencing factors - Yuan Ma; Ziran Zhang; Yuling Yang (Environmental Science and Pollution Research, 2023)

An overview of biological mechanisms and strategies for treating wastewater from printing and dyeing processes - Yuling Song; Lijun Wang; Xi Qiang; Wenhui Gu; Zengling Ma; Guangce Wang (Journal of Water Process Engineering, 2023)

Real-time missing seedling counting in paddy fields based on lightweight network and tracking-by-detection algorithm - Jinrong Cui; Hong Zheng; Zhiwei Zeng; Yuling Yang; Ruijun Ma; Yuyuan Tian; Jianwei Tan; Xiao Feng; Long Qi (Computers and Electronics in Agriculture, 2023)

Corrigendum to “Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China” [Sci. Total Environ. 857 (2023) 159337] - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Coconut shell biochar application in liquid-solid microextraction of triazine herbicides from multi-media environmental samples - Mengge Ma; Zongliang Niu; Zhuhua Tang; Jinyang Bai; Bei Li; Yuling Zhou; Yingying Wen (Analytica Chimica Acta, 2023)

Offshore-onshore tectonomagmatic correlations: Towards a Late Mesozoic non-Andean-type Cathaysian continental margin - Changhai Xu; Yuling Deng; Calvin G. Barnes; Hesheng Shi; Christophe Pascal; Yuanyuan Li; Shunli Gao; Donghui Jiang; Jianlei Xie; Changqian Ma (Earth-Science Reviews, 2023)

Biomass-derived polyphosphazene toward simultaneously enhancing the flame retardancy and mechanical properties of epoxy resins - Yuling Xiao; Xiaowei Mu; Siqi Chen; Guangyong Jiang; Zhoumei Xu; Chao Ma; Lei Song; Yuan Hu (Chemosphere, 2023)

Toxicity of ceria nanoparticles to the regeneration of freshwater planarian Dugesia japonica: The role of biotransformation - Changjian Xie; Xiaowei Li; Lisha Hei; Yiqing Chen; Yuling Dong; Shujing Zhang; Shan Ma; Jianing Xu; Qiuxiang Pang; Iseult Lynch; Zhiling Guo; Peng Zhang (Science of The Total Environment, 2023)

Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Experimental study on adsorption removal of SO2 in flue gas by defective UiO-66 - Yuling Ma; Airong Li; Cheng Wang (Chemical Engineering Journal, 2023)

A novel phosphorus-, nitrogen- and sulfur-containing macromolecule flame retardant for constructing high-performance epoxy resin composites - Guangyong Jiang; Yuling Xiao; Ziyan Qian; Yuting Yang; Pengfei Jia; Lei Song; Yuan Hu; Chao Ma; Zhou Gui (Chemical Engineering Journal, 2023)

Preparation of formate-free PMA@MOF-808 catalysts for deep oxidative desulfurization of model fuels - Cheng Wang; Airong Li; Yuling Ma; Shenglan Qing (Environmental Science and Pollution Research, 2022)

Assimilation Research of Wind Stress Drag Coefficient Based on the Linear Expression - Junli Xu; Yuling Nie; Kai Ma; Wenqi Shi; Xianqing Lv (Journal of Marine Science and Engineering, 2021)
The wind stress drag coefficient plays an important role in storm surge models. This study reveals the influences of wind stress drag coefficients, which are given in form of formulas and inverted by the data assimilation method, on the storm surge levels in the Bohai Sea, Yellow Sea, and East China Sea during Typhoon 7008. In the process of data assimilation, the drag coefficient is based on the linear expression Cd = (a + b × U10) × 10−3 (generally speaking, a and b are empirical parameters determined by observed data). The results showed that the performance of the data assimilation method was far superior to those of drag coefficient formulas. Additionally, the simulated storm surge levels obviously changed in the neighborhood of typhoon eye. Furthermore, the effect of initial values of a and b in the Cd expression on the storm surge levels was also investigated when employing the data assimilation method. The results indicated that the simulation of storm surge level was the closest to the observation when a and b were simultaneously equal to zero, whereas the simulations had slight differences when the initial values of a and b were separately equal to the drag coefficients from the work of Smith, Wu, and Geernaert et al.. Therefore, we should choose appropriate initial values for a and b by using the data assimilation method. As a whole, the data assimilation method is much better than drag coefficient parameterization formulas in the simulation of storm surges.

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Meta-analysis of the effect of the overexpression of aquaporin family genes on the drought stress response - Jianhong Ren; Xiaoxiao Yang; Chunying Ma; Yuling Wang; Juan Zhao; Le Kang (Plant Biotechnology Reports, 2021)

Interleukin-25 in sputum as a marker of airway inflammation in children asthma - Yun Zhang; Cuifen Zhao; Xiuxia Zhao; Qingyu Kong; Mingjie Ding; Yuling Han; Xiang Ma; Lu Cheng (Science China Life Sciences, 2019)

Effects of iron, calcium, and organic matter on phosphorus behavior in fluvo-aquic soil: farmland investigation and aging experiments - Yuling Ma; Jie Ma; Hao Peng; Liping Weng; Yali Chen; Yongtao Li (Journal of Soils and Sediments, 2019)

Impacts of Large-Area Impervious Surfaces on Regional Land Surface Temperature in the Great Pearl River Delta, China - Yuling Ma; Kun Yang; Shaohua Zhang; Mingchan Li (Journal of the Indian Society of Remote Sensing, 2019)

Remediation of Cr(VI)-Contaminated Soil Using the Acidified Hydrazine Hydrate - Yameng Ma; Fangfang Li; Yuling Jiang; Weihua Yang; Lv Lv; Haotian Xue; Yangyang Wang (Bulletin of Environmental Contamination and Toxicology, 2016)

Characterization of a maize ERF gene, ZmERF1, in hormone and stress responses - Qingling Shi; Yongbin Dong; Qiang Zhou; Dahe Qiao; Zhiyan Ma; Long Zhang; Yuling Li (Acta Physiologiae Plantarum, 2016)

Study on the velocity structure of the crust in Southwest Yunnan of the north-south seismic belt—Results from the Menghai-Gengma-Lushui deep seismic sounding profile - ShuaiJun Wang; BaoJin Liu; JianShi Zhang; BaoFeng Liu; YuLing Duan; XiangHui Song; XiaoGuo Deng; CeJun Ma; YiRan Zang (Science China Earth Sciences, 2015)

Isolation and characterization of ZmERF1 encoding ethylene responsive factor-like protein 1 in popcorn (Zea mays L.) - Qingling Shi; Yongbin Dong; Dahe Qiao; Qilei Wang; Zhiyan Ma; Feifei Zhang; Qiang Zhou; He Xu; Fei Deng; Yuling Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Phylogeography and evolution of a fungal–insect association on the T ibetan P lateau - Yongjie Zhang; Shu Zhang; Yuling Li; Shaoli Ma; Chengshu Wang; Meichun Xiang; Xin Liu; Zhiqiang An; Jianping Xu; Xingzhong Liu (Molecular Ecology, 2014)
Parasitoidism refers to a major form of interspecies interactions where parasitoids sterilize and/or kill their hosts typically before hosts reach reproductive age. However, relatively little is known about the evolutionary dynamics of parasitoidism. Here, we investigate the spatial patterns of genetic variation of Chinese cordyceps, including both the parasitoidal fungus Ophiocordyceps sinensis and its host insects. We sampled broadly from alpine regions on the Tibetan Plateau and obtained sequences on seven fungal and three insect DNA fragments from each of the 125 samples. Seven and five divergent lineages/cryptic species were identified within the fungus and host insects, respectively. Our analyses suggested that O . sinensis and host insects originated at similar geographic regions in southern Tibet/Yunnan, followed by range expansion to their current distributions. Cophylogenetic analyses revealed a complex evolutionary relationship between O. sinensis and its host insects. Significant congruence was found between host and parasite phylogenies and the time estimates of divergence were similar, raising the possibility of the occurrence of cospeciation events, but the incongruences suggested that host shifts were also prevalent. Interestingly, one fungal genotype was broadly distributed, consistent with recent gene flow. In contrast, the high‐frequency insect genotypes showed limited geographic distributions. The dominant genotypes from both the fungus and the insect hosts may represent ideal materials from which to develop artificial cultivation of this important Chinese traditional medicine. Our results demonstrate that both historical and contemporary events have played important roles in the phylogeography and evolution of the O. sinensis –ghost moth parasitoidism on the Tibetan Plateau.

Four novel antimicrobial peptides derived from human C8α-MACPF - Zhen Zhang; Yuling Zhou; Jing Sun; Peihong Mao; Xiang Jing; Xiangdong Ma; Lixin Ma (Biotechnology Letters, 2014)

Erratum to: Flavokawain B induces apotosis of non-small cell lung cancer H460 cells via Bax-initiated mitochondrial and JNK pathway - JunXia An; YaRong Gao; Jing Wang; QiYu Zhu; YuLing Ma; Jian Wu; Jian Sun; YaXiong Tang (Biotechnology Letters, 2012)

Flavokawain B induces apoptosis of non-small cell lung cancer H460 cells via Bax-initiated mitochondrial and JNK pathway - JunXia An; YaRong Gao; Jing Wang; QiYu Zhu; YuLing Ma; Jian Wu; Jian Sun; YaXiong Tang (Biotechnology Letters, 2012)

High-level expression and characterization of a highly thermostable chitosanase from Aspergillus fumigatus in Pichia pastoris - Xiaomei Chen; Chao Zhai; Lixin Kang; Chunhua Li; Hong Yan; Yuling Zhou; Xiaolan Yu; Lixin Ma (Biotechnology Letters, 2012)

Pharmacokinetics of Anti-hepcidin Monoclonal Antibody Ab 12B9m and Hepcidin in Cynomolgus Monkeys - Jim J. Xiao; Wojciech Krzyzanski; Yow-Ming Wang; Hongyan Li; Mark J. Rose; Mark Ma; Yuling Wu; Beth Hinkle; Juan Jose Perez-Ruixo (The AAPS Journal, 2010)

Global genome expression analysis of rice in response to drought and high-salinity stresses in shoot, flag leaf, and panicle - Junli Zhou; Xiangfeng Wang; Yuling Jiao; Yonghua Qin; Xigang Liu; Kun He; Chen Chen; Ligeng Ma; Jian Wang; Lizhong Xiong; Qifa Zhang; Liumin Fan; et al. (Plant Molecular Biology, 2007)

The changing regional distribution of grain production in China in the 21st century - Peihong Yin; Xiuqi Fang; Qing Tian; Yuling Ma (Journal of Geographical Sciences, 2006)